Pengembangan Modul PPKn Berbasis Brain Based Learning pada Pembelajaran PPKn Kelas IV Sekolah Dasar - Prasetya, Anantama Rastra; Hidayat, Otib Satibi; Saladin, Andi Ali (Efektor, 2022)
This development analysis aims to supply a product within the variety of social science education modules supported by brain-based learning in civics learning for grade IV in elementary faculties on rights and obligations of society material. Respondents in this study concerned three specialists, particularly material experts, media experts, and linguist experts, further as eleven students in grade IV from SDN Rawamangun 05. the tactic employed in this study was research and development (R&D) with the chosen model, namely ADDIE. There are five steps in ADDIE. The info was collected through interviews, observation, and formative evaluation. The data analysis results showed an average share from a knowledgeable review of 90%. The results of information analysis on a matched take a look at involving three students, and the results obtained 92% and interviews. The results of an exceedingly small cluster test involving eight students were 84%. Thus, the social science Education module supported brain-based learning in social science learning for grade IV in elementary faculties on social rights and obligations material obtained superb criteria and was appropriate for use.